Study on stress evolution law and control technology of roadway formed by roof cutting during crossing overlying remained coal pillar. Issue 2 (March 2023) - Shen, Fuxin; Song, Yanqi; Zheng, Junjie; Zhao, Wenchao; Yang, Minjian; Ma, Hongfa; Shao, Zhixin
The application of roadway formed automatically by roof cutting (RFARC) technology in the working face under the goaf of close distance coal seam greatly improves the mining rate of resources. However, the existence of overlying remained coal pillar (ORCP) makes the stress environment more complex and greatly increases the difficulty of stability control of RFARC. Hence, the 9101 Working face of Xiashanmao Coal Mine was taking as engineering background. In accordance with the principle of RFARC, the process of crossing the ORCP is introduced, and the calculation formula of the bending deformation of roof is proposed. Through numerical analysis and field test, the stress evolution law of stope and RFARC in the process of crossing ORCP is analyzed. The results show that in the process of crossing the ORCP, the peak stress value of the solid coal side of the RFARC increases continuously, whereas, the stress values of the roof and floor and the gob-side are small. The stress value and caving step distance of roof cutting side of working face are less than those without roof cutting. The stress of stope and RFARC tends to be stable when the working face is lagged 80 m. The combined supporting measures composed of constant resistance and large deformation (CRLD) anchor cable, hydraulic prop and unit support can effectively control the deformation of RFARC. This work provides an effective and economical method to non-pillar mining affected by ORCP in close distance coal seam.